Analytical/numerical hybrid solution for one-dimensional ablation problem - Kurokawa, Fábio Yukio [UNESP]; Diniz, Antonio João [UNESP]; Campos-Silva, João Batista [UNESP] (ASME International, 2003)
Ablation is a thermal protection process with several applications in engineering, mainly in the field of airspace industry. The use of conventional materials must be quite restricted, because they would suffer catastrophic flaws due to thermal degradation of their structures. However, the same materials can be quite suitable once being protected by well-known ablative materials. The process that involves the ablative phenomena is complex, could involve the whole or partial loss of material that is sacrificed for absorption of energy. The analysis of the ablative process in a blunt body with revolution geometry will be made on the stagnation point area that can be simplified as a one-dimensional plane plate problem, hi this work the Generalized Integral Transform Technique (GITT) is employed for the solution of the non-linear system of coupled partial differential equations that model the phenomena. The solution of the problem is obtained by transforming the non-linear partial differential equation system to a system of coupled first order ordinary differential equations and then solving it by using well-established numerical routines. The results of interest such as the temperature field, the depth and the rate of removal of the ablative material are presented and compared with those ones available in the open literature.
Keywords: Generalized integral transform technique (GITT); Thermal protections; Absorption; Aerospace engineering; Boundary conditions; Heat flux; Heat transfer; Mass transfer; Ordinary differential equations; Partial differential equations; Pyrolysis; Specific heat; Ablation